CERPEN ANGLANGKAHI KARANG ULU DAN CERPEN MERTA MATEMAHAN WISIA KARYA I MADE SUARSA ANALISIS SOSIOLOGI SASTRA - Arum Trisnanti Utami, Nyoman Dewi (Humanis, 2013)
This study examines the literary short stories about Anglangkahi Karang Ulu and short stories Merta Matemahan Wisia that contained in Pupulan 12 Carita Cutet Basa Bali Merta Matemahan Wisia by I Made Suarsa to discusses the main problems of the structures and the social aspects that exist in this short story. The theory that used in this study is the structural theory and the theory of sociology of literature, while the methods and techniques include, provision of stage data using the method of observation and interviews, assisted with the recording techniques, and translation techniques. Stage of data processing using the qualitative methods aided by descriptive analytic techniques, and the presentation of the results of the data analysis stage using informal methods aided by deductive and inductive techniques. Theoretical basis is used based on the structural Teeuw’s opinion. The foundation of the theory of sociology of literature are used based on the opinions of Wellek and Warren, the author as the creator of literature and sociology literature linking literature with the social aspects in it. The results obtained in this study establish the unfolding narrative structure of short stories Anglangkahi Karang Ulu and short stories Merta Matemahan Wisia incident, plot, character and characterization, theme, and the mandate. Social aspects contained in the short stories Anglangkahi Karang Ulu and short stories Merta Matemahan Wisia covering aspects of religion, forms of marriage, naming aspect, and the aspect of trust.
Keywords: short story, sociology, literature.